2023
DOI: 10.1007/s40257-023-00788-2
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Apremilast for the Treatment of Japanese Patients with Palmoplantar Pustulosis: Results from a Phase 2, Randomized, Placebo-Controlled Study

Abstract: Background Palmoplantar pustulosis (PPP) is a pruritic, painful, recurrent, and chronic dermatitis with limited therapeutic options. Objective To evaluate the efficacy and safety of apremilast for the treatment of Japanese patients with PPP and inadequate response to topical treatment. Methods This phase 2, randomized, double-blind, placebo-controlled study enrolled patients with Palmoplantar Pustulosis Area and Severity Index (PPPASI) total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…While both apremilast and guselkumab have been shown to be beneficial for PAO, 4 , 5 the efficacy of guselkumab for skin lesions may not be as compelling as apremilast; only approximately half of the patients achieved 50% improvement by guselkumab, whereas 78.3% of patients on apremilast achieved the same level of improvement in clinical trials. 6 , 7 , 8 In addition, a sub‐analysis by the Pharmaceuticals and Medical Devices Agency, the drug regulatory authority of Japan, suggested that the effectiveness of guselkumab in nonsmokers may be low. 9 Furthermore, biologics including guselkumab, are generally more economically burdensome than apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…While both apremilast and guselkumab have been shown to be beneficial for PAO, 4 , 5 the efficacy of guselkumab for skin lesions may not be as compelling as apremilast; only approximately half of the patients achieved 50% improvement by guselkumab, whereas 78.3% of patients on apremilast achieved the same level of improvement in clinical trials. 6 , 7 , 8 In addition, a sub‐analysis by the Pharmaceuticals and Medical Devices Agency, the drug regulatory authority of Japan, suggested that the effectiveness of guselkumab in nonsmokers may be low. 9 Furthermore, biologics including guselkumab, are generally more economically burdensome than apremilast.…”
Section: Discussionmentioning
confidence: 99%